Visualization of fidaxomicin association with the exosporium layer of Clostridioides difficile spores. (June 2021) - Bassères, Eugénie; Endres, Bradley T.; Montes-Bravo, Nicolás; Pérez-Soto, Nicolás; Rashid, Tasnuva; Lancaster, Christopher; Begum, Khurshida; Alam, M. Jahangir; Paredes-Sabja, Daniel; Garey, Kevin W.
Abstract: Background: Fidaxomicin has novel pharmacologic effects on C. difficile spore formation including outgrowth inhibition and persistent spore attachment. However, the mechanism of fidaxomicin attachment on spores has not undergone rigorous microscopic studies. Materials & methods: Fidaxomicin attachment to C. difficile spores of three distinct ribotypes and C. difficile mutant spores with inactivation of exosporium or spore-coat protein-coding genes were visualized using confocal microscopy with a fidaxomicin-bodipy compound (green fluorescence). The pharmacologic effect of the fidaxomicin-bodipy compound was determined. Confocal microscopy experiments included direct effect on C. difficile wild-type and mutant spores, effect of exosporium removal, and direct attachment to a comparator spore forming organism, Bacillus subtilis . Results: The fidaxomicin-bodipy compound MIC was 1 mg/L compared to 0.06 mg/L for unlabeled fidaxomicin, a 16-fold increase. Using confocal microscopy, the intracellular localization of fidaxomicin into vegetative C. difficile cells was observed consistent with its RNA polymerase mechanism of action and inhibited spore outgrowth. The fidaxomicin-bodipy compound was visualized outside of the core of C. difficile spores with no co-localization with the membrane staining dye FM4-64. Exosporium removal reduced fidaxomicin-bodipy association with C. difficile spores. Reduced fidaxomicin-bodipy was observed in C. difficile mutant spores for the spore surface proteins CdeC and CotE. Conclusion: This study visualized a direct attachment of fidaxomicin to C. difficile spores that was diminished with mutants of specific exosporium and spore coat proteins. These data provide advanced insight regarding the anti-spore properties of fidaxomicin. Highlights: A direct attachment of Clostridoiodes difficile spores by fidaxomicin was observed by confocal microscopy. Exosporium removal reduced attachment especially if certain surface proteins were removed. This pharmacologic property may elucidate another mechanism that reduces the likelihood of C. difficile infection recurrence with fidaxomicin.